2015
DOI: 10.1097/md.0000000000000874
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Laparoscopic Surgery in the Management of Children and Adolescents With Inflammatory Bowel Disease

Abstract: Although laparoscopic surgery is readily used in the management of inflammatory bowel disease (IBD) in adults, its role in the surgical treatment of IBD in the pediatric population is not well established. The aim of this narrative review was to analyze the published evidence comparing laparoscopic and open resection in the management of children and adolescents with IBD.The Pubmed and Embase databases were searched using the terms “inflammatory bowel disease,” “children,” “adolescents,” “laparoscopic,” and “c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 20 publications
7
58
0
1
Order By: Relevance
“…20 GSEA also clearly showed that OxPhos and MRP genes sets were distinctively downregulated in thyroid cancer tissues. 21 Through bioinformatics analysis, Lee et al identified that the mitochondrial calcium transporter LETM1 was associated cellular growth signals such as the insulin signaling pathway, and it was up-regulated in aggressive thyroid cancer. 22 Detailed studies about important circRNAs in thyroid cancer are limited.…”
Section: Resultsmentioning
confidence: 99%
“…20 GSEA also clearly showed that OxPhos and MRP genes sets were distinctively downregulated in thyroid cancer tissues. 21 Through bioinformatics analysis, Lee et al identified that the mitochondrial calcium transporter LETM1 was associated cellular growth signals such as the insulin signaling pathway, and it was up-regulated in aggressive thyroid cancer. 22 Detailed studies about important circRNAs in thyroid cancer are limited.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of patients with bone metastasis require treatment, yet bone metastasis is notoriously challenging for clinical management, especially unresectable bone metastasis, which underlies the importance of palliative interventions. 13 Previous studies have shown that 125 I seed implantation treatment resulted in a median progressionfree survival of 12.5 months with local control rates of 3, 6 and 12 months at 100%, 95% and 60%, respectively. The median survival time of all patients was 16 months.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Di Monaco et al documented that for women with hip-fractures, handgrip strength measured before rehabilitation was correlated weakly but significantly (p=0.001) with Barthel Index scores at the end of inpatient rehabilitation (r partial =0.25) and at 6-month follow-up (r partial =0.28). 106 Hashimoto et al demonstrated that preoperative grip strength was significantly greater (p=0.001) among patients who used a step-over-step pattern rather than a step-to-step pattern to negotiate stairs one year post total knee arthroplasty. 107 Incidentally, they also found preoperative grip strength to be better than preoperative knee extension strength for predicting the pattern used to negotiate stairs.…”
Section: Grip Strength As a Biomarker Of Future Outcomesmentioning
confidence: 99%